Efeito de amostra finita na espectroscopia de espelho térmico - Zanuto, Vitor Santaella (2012)
The thermal mirror method has been widely investigated both theoretically and experimentally over the past few years. The thermal mirror technique relies on measuring the time evolution of a laser induced thermoelastic displacement in solid sample. The amplitude of this effect is directly related to the optical absorption coefficient and thermal expansion coefficient. In addition, the time evolution depends on the thermal diffusion properties. Monitoring this dynamic effect allow us to access thermal optical and mechanical properties of the materials. Effects as fluid heat coupling and sample size has been considered as improvement of the initial model. Here, we consider experimental results to validated the sample size effects on the physical properties of different optical glasses. We show that consistent physical properties could be obtained when sample thickness is taken into account.